Post-Topotecan Mixed Response and ‘Redifferentiation-akin’ Phenomenon on Dual Tracer PET-CT in Multiple Treatment-Resistant Metastatic Neuroendocrine Neoplasm - Loharkar, Sarvesh; Basu, Sandip (World Journal of Nuclear Medicine, 2023)
A 50-year-old female patient of heavily pre-treated (chemotherapy and multiple treatment-resistant) and progressive intermediate-grade metastatic neuroendocrine neoplasm is presented, wherein the lesions showed mixed response following topotecan treatment and multiple hepatic metastasis showed increase in the SSTR expression and decrease in FDG concentration on dual-tracer PET/CT (68Ga-DOTATATE and 18F-FDG PET/CT). Such observation allowed 177Lu-DOTATATE PRRT to be considered for an advanced, symptomatic, and multiple treatment-resistant patient with limited palliative treatment options left.
Keywords: neuroendocrine neoplasm; topotecan; 68Ga-DOTATATE; PET-CT; peptide receptor radionuclide therapy